MACLEAYA CORDATA EXTRACT AND SANGROVIT GENOTOXICITY. ASSESSMENT IN VIVO - Stiborova, Marie; Vostalova, Jitka; Zdarilova, Adela; Ulrichova, Jitka; Hudecek, Jiri; Tschirner, Kathrin; Simanek, Vilim (Biomedical papers, 2008)
Background: Sanguinarine (SG) has been reported to form DNA adducts in vitro and increase the levels of DNA single strand breaks in the blood and bone marrow of mice treated intraperitoneally with SG. Recently, we showed no genotoxic effects of orally administrated 120 mg/kg feed Macleaya cordata extract (a mixture of sanguinarine and chelerythrine) in pigs or rats in 90-day studies. The goal of this paper was to assess the possible genotoxicity of M. cordata extract when included as a dietary admixture to rodents at concentrations providing 600 mg/kg feed and 100, 7000 or 14000 mg/kg feed Sangrovit (natural feed additive containing M. cordata extract and powdered M. cordata) in a 90-day pilot study.Methods and Results: The rats consumed ad libitum either the standard diet or the diets containing 367 ppm of sanguinarine and chelerythrine in M. cordata extract, and 5, 330, or 660 ppm of total alkaloids in Sangrovit for 90 days. The DNA adducts formation in liver was analyzed by 32P-postlabeling technique and DNA single strand breaks in lymphocytes were evaluated by Comet assay. The results showed that M. cordata extract and/or Sangrovit induced no DNA damage to rat lymphocytes or hepatocytes after 90-days oral administration.Conclusions: Data from the studies described in this paper and the fact that Sangrovit given to the rats in our experiments were higher than the recommended dose (50 to 100 mg/kg feed), argue strongly in favour of the use of Sangrovit in live stock.
Keywords: Recevied: May 15; 2008; Accepted: May 28; 2008